Strengths, Limitations and Challenges in the Implementation of Active Learning in an Undergraduate Course of Logistics Technology - Novais, Andre Seixas de [UNESP]; Silva, Messias Borges [UNESP]; Muniz, Jorge [UNESP] (Tempus Publications, 2017)
Teaching strategies have been used by several Higher Education Institutions to improve learning rates. In this context, international surveys have identified Active Learning as a methodology that provides students with the ability to be coauthors of their own learning process in which they occupy the central role. Professors also play an important role of process mediators through this methodology. Thus, strategies such as problem-based learning, collaborative learning, peer assessment, flipped classroom, among others, have been identified by experts as Active Learning approaches that increase learning rates. It so happens because it improves autonomy in reading, self-learning, discussions in pairs, information sharing, researches and discoveries. Despite the foregoing, Active Learning implementation in a higher education course is not an easy task, thence this research seeks answers to the following question: What are the main strengths, limitations and challenges to implement Active Learning in a higher education institution?''. In order to answer such a question, this paper aims to present a case study on the implementation of Active Learning in a higher education program. The object of this research is an undergraduate course in Logistics Technology of a Brazilian institution, with emphasis on its implementation actions, feedback from students and professors and experiences obtained from the discipline of Statistical Methods, which is considered as pilot project. In order to better understand its theory, a literature review of Active Methodology is going to be presented in the first and second sections, the third section is going to highlight some international experiences, its methods are going to be presented in the fourth section, and discussions of the case study and research conclusions are going to be shown in the fifth and sixth sections, respectively.
Keywords: active learning; strengths; limitations; challenges; implementation; higher education; logistics